Functional Dissociation of Confident and Not-Confident Errors in the Spatial Delayed Response Task Demonstrates Impairments in Working Memory Encoding and Maintenance in Schizophrenia - Mayer, Jutta S.; Stäblein, Michael; Oertel-Knöchel, Viola; Fiebach, Christian J. (Frontiers in Psychiatry, 2018)
Even though extensively investigated, the nature of working memory deficits in patients with schizophrenia is not yet fully understood. In particular, the contribution of different working memory sub-processes to the severe working memory deficit observed in patients with schizophrenia is a matter of debate. So far, most research has focused on impaired working memory maintenance. By analyzing different types of errors in a spatial delayed response task, we have recently demonstrated that incorrect yet confident responses (which we labeled as false memory errors) rather than incorrect/ not-confident responses reflect failures of working memory encoding, which was also impaired in patients with schizophrenia. In the present study, we provide further evidence for a functional dissociation between confident and not-confident errors by manipulating the demands on working memory maintenance, i.e., the length over which information has to be maintained in working memory. Furthermore, we investigate whether these functionally distinguishable working memory processes are impaired in patients with schizophrenia. Twenty-four patients with schizophrenia and 24 demographically matched healthy controls performed a spatial delayed response task in which the length of the delay period was varied between 1, 2, 4, and 6 seconds. In each trial, participants also rated their level of response confidence. Across both groups, longer delays led to increased rates of incorrect/ not-confident responses, while incorrect/ confident responses were not affected by delay length. This functional dissociation provides additional support for our proposal that false memory errors (i.e., confident errors) reflect problems at the level of working memory encoding, while not-confident errors reflect failures of working memory maintenance. Schizophrenic patients showed increased numbers of both confident and not-confident errors, suggesting that both sub-processes of working memory – encoding and maintenance – are impaired in schizophrenia. Combined with the delay length-dependent functional dissociation, we propose that these impairments in schizophrenic patients are functionally distinguishable.